Filtering Characteristics of Phonon Polaritons Waves Based on Dielectric-h-BN-Dielectric Structure in Mid-Infrared Band - Ming Cai; Shulong Wang; Zhihong Liu; Yindi Wang; Tao Han; Hongxia Liu (Nanomaterials, 2020)
Hyperbolic materials can be used to excite hyperbolic phonon polaritons in specific frequency bands, which causes abrupt interfaces with fluctuations of permittivity and different transmission characteristics at different incident wavelengths. Using the quasi-static approximation, the filtering characteristics of hexagonal Boron nitride (h-BN) and the transmission characteristics of phonon polaritons waves on a dielectric-h-BN-dielectric structure were studied in the paper. The results show that a smaller relative permittivity of the materials above and below h-BN and a thicker h-BN (ε1 = 1 (air), ε2 = 3.9 (SiO2), d = 100 nm) will lead to better filtering characteristics for different wavenumbers’ incident waves (propagation length from 0.0028 μm to 1.9756 μm). Simulation results in COMSOL validated the previous theoretical calculations. Moreover, the transmissivity and 3dB bandwidth of the type-II band were calculated with different structure widths. The maximum transmissivity of ~99% appears at a width of 100 nm, and the minimum 3dB bandwidth reaches 86.35 cm−1 at a structure width of 1300 nm. When the structure width meets or exceeds 1700 nm, the 3dB bandwidth is equal to 0, and its structure length is the limit for the filter application. These characteristics reveal the excellent filtering characteristics of the dielectric-h-BN-dielectric structure, and reveal the great potential of using the dielectric-h-BN-dielectric structure to design optical filter devices with excellent performance in mid-infrared bands.